Performance of staggered bit island spacing adjustment for a SRTR BPMR system - M. Mattayakan; S. Koonkarnkhai; P. Kovintavewat; C. Warisarn (My University, 2023)
One of the key problems facing the designer of data storage devices is how to handle the exponential rise in demand for information storage. To enhance the storage capacity of bit-patterned magnetic recording (BPMR) that stores one data bit in a single magnetic island, the spacing among bit islands, i.e., bit period and track pitch, must be reduced. However, the interference effects from both the across- and along-track directions are unavoidably increased, which leads to performance degradation. This paper proposes to utilize the proper spacing arrangement of magnetic islands for a single-reader two-track reading scheme to increase the staggered BPMR system’s storage capacity. We also study how the system performs for different distances between magnetic islands when track misregistration and media noise are present. Simulation results reveal that the staggered BPMR system with an appropriate magnetic island spacing can provide better performance than the traditional island placement, where the spacing between bit islands in across- and along-track directions is same.
Keywords: Patterned media; Bit (key); Magnetic storage; Advanced Data Storage Technologies